2021
DOI: 10.1111/1541-4337.12860
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of the efficacy of processing stages and interventions for controllingCampylobactercontamination during broiler chicken processing

Abstract: Systematic review and meta-analysis were conducted to quantify the effects of processing stages and interventions on the prevalence and concentration of Campylobacter on broiler carcasses. To comprehensively capture relevant evidence, six databases were searched using the keywords "Campylobacter" and "broiler chicken." The literature search yielded 10,450 unique citations, and after applying predetermined inclusion and exclusion criteria, 72 and 53 relevant citations were included in meta-analyses for processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 160 publications
4
2
0
Order By: Relevance
“…However, treatment with water alone had the lowest reduction of all the immersion interventions. These findings are in agreement with a meta-analysis by Dogan et al (2021) which observed that immersion treatment without antimicrobial additives during primary chilling reduced Campylobacter , but immersion chilling with antimicrobial additives resulted in larger reductions. On the other hand, a meta-analysis by Bucher et al (2012) that evaluated the effect of primary chilling on Salmonella reported varying results for immersion chilling in water alone.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…However, treatment with water alone had the lowest reduction of all the immersion interventions. These findings are in agreement with a meta-analysis by Dogan et al (2021) which observed that immersion treatment without antimicrobial additives during primary chilling reduced Campylobacter , but immersion chilling with antimicrobial additives resulted in larger reductions. On the other hand, a meta-analysis by Bucher et al (2012) that evaluated the effect of primary chilling on Salmonella reported varying results for immersion chilling in water alone.…”
Section: Discussionsupporting
confidence: 92%
“…The results found that air chilling had the lowest reduction in population and prevalence for Campylobacter compared to all other full chill interventions. Similar results were seen in other meta-analyses examining primary chilling of Salmonella and Campylobacter ( Bucher et al, 2012 ; Dogan et al, 2021) .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations